Resistance Performance of a Ship in Model-Scaled Brash Ice Fields Using CFD and DEM Coupling Model - Xie, Chang; Zhou, Li; Wu, Tiecheng; Liu, Renwei; Zheng, Sijie; Tsuprik, Vladimir G.; Bekker, Alexander (Frontiers in Energy Research, 2022)
The brash ice channel formed with icebreaker navigation is a normal working scenario for ice-going vessels. Therefore, it is necessary to study brash ice resistance in this condition. In this study, CFD and DEM coupling methods were adopted to investigate the resistance performance of a ship sailing in model-scaled brash ice fields, considering the collision force and friction resistance, among the brash ice, and the water resistance and hydrodynamic force of brash ice, which make up physical scenarios of navigation in the brash ice channel. To study the effect of aforementioned parameters on the average total resistance, the time step, iteration, and brash ice stiffness were analyzed; we found that a time step of 0.02 s, iteration of 10, and brash ice stiffness of 1000 N/m that showed better repeatability of the physical phenomenon, and it was used to reproduce working conditions created in the HSVA ice tank test. The error between the numerical simulation results and the test results is less than 5%, which shows the robustness of the present coupling strategy. Finally, the effects of ship–ice friction coefficient, ice thickness, ice shape, brash ice channel width, and ice concentration on the resistance of the ship were investigated and verified with the published results.